Preventing Mosquito Bite: Perceptions & Practices among Medical Students (GAIMS Journal of Medical Sciences, 2023)
Background: Mosquito borne diseases remain a major public health challenge and contribute to annual outbreaks in India and in the world. Individual awareness and involvement is an important aspect of disease prevention and control. The aim of our study was to assess mosquito bite perceptions and preventive practices among medical students.Methods: A cross sectional study was conducted among undergraduate medical students using convenient sampling method.  Data was collected using semi-structured questionnaire and analyzed with SPSS software version 20.Results: Among 258 study participants majority perceived that they are at risk of mosquito borne diseases which can be prevented. Mosquito repellant creams and full sleeve clothes were the most commonly resorted measures against mosquito bite. No significant association was observed between gender, history of disease and hospitalization with frequency of using the protective measures against mosquito bite.Conclusions: Behavior change at individual level is essential for preventing mosquito bite; adoption of proper preventive practices needs to be emphasized among medical students and all concerned. The health campaigns should ensure that the knowledge acquired is put into practice.